2016
DOI: 10.1038/ismej.2016.5
|View full text |Cite
|
Sign up to set email alerts
|

Insect pathogenicity in plant-beneficial pseudomonads: phylogenetic distribution and comparative genomics

Abstract: Bacteria of the genus Pseudomonas occupy diverse environments. The Pseudomonas fluorescens group is particularly well-known for its plant-beneficial properties including pathogen suppression. Recent observations that some strains of this group also cause lethal infections in insect larvae, however, point to a more versatile ecology of these bacteria. We show that 26 P. fluorescens group strains, isolated from three continents and covering three phylogenetically distinct sub-clades, exhibited different activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
187
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 133 publications
(203 citation statements)
references
References 82 publications
9
187
0
Order By: Relevance
“…As for the fourth subgroup, the two strains CMR5c and CMR12a were isolated from the rhizosphere of cocoyam in Cameroon among other closely related isolates and were selected for their ability to supress cocoyam root rot disease (Perneel et al, ). These two strains have been successively affiliated to the Pseudomonas putida species complex (Mavrodi et al, ) and, more recently, to the Pseudomonas fluorescens species complex (Ruffner et al, ; Flury et al, ). Our finding confirms the later affiliation, as P. protegens is currently the closest described species to these two strains.…”
Section: Resultsmentioning
confidence: 99%
“…As for the fourth subgroup, the two strains CMR5c and CMR12a were isolated from the rhizosphere of cocoyam in Cameroon among other closely related isolates and were selected for their ability to supress cocoyam root rot disease (Perneel et al, ). These two strains have been successively affiliated to the Pseudomonas putida species complex (Mavrodi et al, ) and, more recently, to the Pseudomonas fluorescens species complex (Ruffner et al, ; Flury et al, ). Our finding confirms the later affiliation, as P. protegens is currently the closest described species to these two strains.…”
Section: Resultsmentioning
confidence: 99%
“…et al, 2012). An examination of genome sequences published by Flury et al (2016) and other investigators indicated that fluorescent pseudomonads harbor only one copy of phlD , phzF , or prnD per cell. Accordingly, we did not find any significant difference between the abundances of phlD and phzF quantified by qPCR or a cultivation-dependent endpoint dilution assay in samples from Taenikon (Supplementary Figure S4).…”
Section: Discussionmentioning
confidence: 99%
“…Since all in vivo standard curves were prepared with bacterial cells recovered from wheat roots, the CT values can be directly converted to numbers of bacteria harboring phlD , phzF , or prnD per g root. Our qPCR data also directly reflect the abundance of the antimicrobial biosynthesis genes because phlD, phzF , or prnD are present in single copy in genomes of the P. fluorescens group (Flury et al, 2016). A survey of published bacterial genomes revealed that phzF and prnD are also found as a single copy in other bacterial species such as Burkholderia ( phzF and prnD ), Pectobacterium ( phzF ) or Serratia ( prnD ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas sp. CMR12a is an uncharacterized new species that is taxonomically positioned between P. protegens and P. chlororaphis in the P. fluorescens group (Ruffner et al, 2015, Flury et al, 2016. Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%